2006
DOI: 10.1177/216507990605400105
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries among Ultrasound Sonographers in Rural Manitoba

Abstract: The purpose of this study was to compare the epidemiology of musculoskeletal injuries and workplace ergonomics among rural-based sonographers compared to urban-based sonographers. The authors also tested the use of a biomechanical software program to assess load on the spine and upper extremity joints. A mail-in survey was sent to all practicing sonographers in rural Manitoba, and on-site video-taped ergonomic and biomechanical evaluations were completed for four sites. Rural-based sonographers appear to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 7 publications
3
37
0
1
Order By: Relevance
“…Therefore, left sided scans produced larger moment arms about the shoulder joint ( Figure 2). These findings are consistent with the biomechanical assessment by Friesen et al (2006) which concluded that load moments were the highest when shoulder abduction was greatest and elbow flexion was smallest. Forceful manual exertions are commonly cited as risk factors for musculoskeletal disorders (Punnett & Wegman, 2004;Bernard, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, left sided scans produced larger moment arms about the shoulder joint ( Figure 2). These findings are consistent with the biomechanical assessment by Friesen et al (2006) which concluded that load moments were the highest when shoulder abduction was greatest and elbow flexion was smallest. Forceful manual exertions are commonly cited as risk factors for musculoskeletal disorders (Punnett & Wegman, 2004;Bernard, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Friesen et al (2006) reported that sonographers scanned approximately 12 to 14 patients per day, and Pike at al. (1997) reported that sonographers scanned approximately 25 -35 patients per week.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of sonographers in the United Kingdom have had a career‐ending injury as the result of a WRMSD . Poor posture and applying sustained pressure with the US transducer, in addition to poor equipment design and poorly planned scanning sessions, are the main risk factors for WRMSDs in US examinations . Advances in the field of US imaging have increased demands on the service and hence increased the workload of sonographers, with fewer opportunities to incorporate rest breaks within the workday.…”
mentioning
confidence: 99%
“…In one of the few studies to involve only CS, Smith et al (1997) identified three factors that differed between survey respondents with and without MSK pain, including stature, number of exams performed each month, and exam duration. From other studies of the general population of sonographers, factors associated with MSK pain in multiple studies include shoulder abduction, applying sustained pressure with the hand-held transducer, forceful gripping of the transducer, and scanning larger patients (Friesen et al, 2006; Muir et al, 2004; Russo et al, 2002). Average push and grip forces on the transducer have been estimated to range from 1 to 8 kg, depending on the scan type and location (Burnett & Campbell-Kyureghyan, 2010; Village & Trask, 2007).…”
Section: Introductionmentioning
confidence: 99%